2019
DOI: 10.1007/s13592-019-00637-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nosema microsporidians in commercial bumblebees (Bombus terrestris) is not related to the intensity of their use at the landscape scale

Abstract: The use of commercial bumblebees to aid crop pollination may result in overcrowding of agricultural landscapes by pollinators. Consequently, transmission of parasites between pollinators via shared flowers may be substantial. In SW Spain, we assessed the initial infection status of commercial Bombus terrestris colonies and then explored spatial and seasonal influences on changes in parasite prevalence across a landscape where bumblebee colonies are intensively used to pollinate berry crops. Colonies were place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Graystok et al [ 27 ] found molecular evidence for the presence of N. ceranae in the fat body of bumblebees, suggesting the migration of N. ceranae from the gut to this organ [ 27 ]. The fat body is also invaded by the microsporidia Nosema bombi in bumblebee infections [ 72 , 73 ]. However, further analyses are needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Graystok et al [ 27 ] found molecular evidence for the presence of N. ceranae in the fat body of bumblebees, suggesting the migration of N. ceranae from the gut to this organ [ 27 ]. The fat body is also invaded by the microsporidia Nosema bombi in bumblebee infections [ 72 , 73 ]. However, further analyses are needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of hybridization are hard to predict, but displacing the locally adapted genotype is likely to reduce the species fitness. In fact, there have been observations that native subspecies densities decline nearby greenhouses, where commercial subspecies are more prevalent (Trillo et al, 2019), indicating a potential competitive displacing. This is not surprising as the newly arrived genotypes are maintained by a huge propagule pressure, hence, their populations are subsidized and do not depend on their performance in natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Iberian Peninsula the native subspecies is B. t. lusitanicus, a taxon characterized by its distinctive legs with reddish setae (Rasmont, Coppee, Michez, & De Meulemeester, 2008). Recent studies show that the commercial subspecies actively forage in natural areas and can produce viable queens (Trillo, Brown, & Vilà, 2019). Hence, we set up a sampling and genotyping protocol to evaluate the presence and prevalence of hybridization between commercial individuals and the native subspecies.…”
Section: Introductionmentioning
confidence: 99%
“…The climate is typically Mediterranean with very mild winters. In January, the coldest month, the mean of the maximum temperatures is 16.2°C (AEMET, 2015), allowing bumblebee foraging activity (Trillo et al, 2019a).…”
Section: Study Systemmentioning
confidence: 99%
“…For example, besides influencing the provision of pollination services to crops (Desjardins and De Oliveira, 2006;Garibaldi et al, 2013;Marqués et al, 2019) and wild plant communities (Diekötter et al, 2010;Holzschuh et al, 2011), it might affect the success of the bumblebee colonies themselves, which would depend on the quality of crop resources and on how other wild floral resources complement their needs (Westphal et al, 2009). The spillover of commercial bumblebees into natural habitats is also not free of environmental risks, such as the spread of parasites (Colla et al, 2006;Meeus et al, 2011;Trillo et al, 2019a), hybridisation (Cejas et al, 2019;Seabra et al, 2019) and resource competition (Matsumura et al, 2004;Morales et al, 2013) with native pollinators. Therefore, a comprehensive understanding of the factors influencing pollinator spillover in agroecosystems is essential to optimise crop pollination, while preserving the diversity and functioning of wild plant-pollinator communities in adjacent habitats.…”
Section: Conclusion and Potential Implicationsmentioning
confidence: 99%